The protective effect and mechanism of the FXR agonist obeticholic acid via targeting gut microbiota in non-alcoholic fatty liver disease - Zhang DY; Zhu L; Liu HN; Tseng YJ; Weng SQ; Liu TT; Dong L; Shen XZ (Dove Medical Press, 2019)
Dan-Ying Zhang,1,* Lin Zhu,2,* Hai-Ning Liu,1,* Yu-Jen Tseng,3 Shu-Qiang Weng,1 Tao-Tao Liu,1 Ling Dong,1 Xi-Zhong Shen1,41Department of Gastroenterology, Zhongshan Hospital of Fudan University, Shanghai 200032, People’s Republic of China; 2Department of Geriatrics, Zhongshan Hospital of Fudan University, Shanghai 200032, People’s Republic of China; 3Department of Gastroenterology, Huashan Hospital of Fudan University, Shanghai 200040, People’s Republic of China; 4Shanghai Institute of Liver Diseases, Zhongshan Hospital of Fudan University, Shanghai 200032, People’s Republic of China*These authors contributed equally to this workBackground: It is reported that various diseases such as non-alcoholic fatty liver disease (NAFLD) are associated with imbalance of microbiome. And FXR has been well investigated in liver diseases.Purpose: The objective of this study was to identify the role of farnesoid X receptor agonist obeticholic acid via targeting gut microbiota in NAFLD.Patients and methods: Male C57BL/6 mice were fed either a normal-chow diet or a high-fat diet (HFD). Obeticholic acid(30mg/(kg·d)) and/or a combination of antibiotics were administered orally by gavage to mice for 12 weeks. Gut microbiota profiles were established through 16S rRNA amplicon sequencing. The effects of obeticholic acid on liver inflammation, the gut barrier, endotoxemia, gut microbiome and composition of the bile acid were also investigated.Results: Obeticholic acid treatment can significantly improve obesity, circulation metabolism disorders, liver inflammation and fibrosis, and intestinal barrier damage caused by HFD. Removal of normal commensal bacteria can weaken the effect of obeticholic acid. The gut microbial structure was changed, and abundance of Blautia was increased significantly after treated with obeticholic acid. After obeticholic acid treatment, the concentration of taurine-bound bile acid caused by HFD was reduced in the liver.Conclusion: Taken together, these data suggest that obeticholic acid has aprotective effect on NAFLD via changing the components of gut microbiota, specifically increasing the abundance of Blautia.Keywords: non-alcoholic fatty liver disease, farnesoid X receptor, gastrointestinal microbiome, bile acid, metabolic diseases